Exploring sex differences in blood-based biomarkers following exhaustive exercise using bioinformatics analysis - Blumkaitis, Julia C.; Nunes, Natalia; Strepp, Tilmann; Tomaskovic, Aleksandar; Wenger, Mario; Widauer, Hannah; Aglas, Lorenz; Simon, Perikles; Stöggl, Thomas Leonhard; Haller, Nils (Biology of Sport, 2024)
This study examined the acute effects of exercise testing on immunology markers, established blood-based biomarkers, and questionnaires in endurance athletes, with a focus on biological sex differences. Twenty-four healthy endurance-trained participants (16 men, age: 29.2±7.6 years, maximal oxygen uptake (V̇ O 2max ): 59.4±7.5 ml·min −1 · kg −1 ; 8 women, age: 26.8±6.1 years, V̇ O 2max : 52.9±3.1 ml·min −1 · kg −1 ) completed an incremental submaximal exercise test and a ramp test. The study employed exploratory bioinformatics analysis: mixed ANOVA, k-means clustering, and uniform manifold approximation and projection, to assess the effects of exhaustive exercise on biomarkers and questionnaires. Significant increases in biomarkers (lymphocytes, platelets, procalcitonin, hemoglobin, hematocrit, red blood cells, cell-free DNA (cfDNA)) and fatigue were observed post-exercise. Furthermore, differences pre- to post-exercise were observed in cytokines, cfDNA, and other blood biomarkers between male and female participants. Three distinct groups of athletes with differing proportions of females (Cluster 1: 100% female, Cluster 2: 85% male, Cluster 3: 37.5% female and 65.5% male) were identified with k-means clustering. Specific biomarkers (e.g., interleukin-2 (IL-2), IL-10, and IL-13, as well as cfDNA) served as primary markers for each cluster, potentially informing individualized exercise responses. In conclusion, our study identified exercise-sensitive biomarkers and provides valuable insights into the relationships between biological sex and biomarker responses.